SOCIAL APPROACH IN TAFSIR AL-QUR’AN PERSPECTIVE OF HASAN HANAFI - Ade Jamaruddin (Jurnal Ushuluddin, 2015)
Hasan Hanafi states that a thorough revival in religious reforms affects social revolution and Muslims’ politics, interpretation methodologies are needed go beyond the textual and historical interpretations, which do not take al-Qur’an in a narrow space and time in Rasulullah period, Hasan Hanafi gave a social approach in interpreting the Qur’an (almanhaj al-ijtima’i Fi at-Tafsir). With this interpretation, according to Hanafi, an exegete who want to find the meaning of al-Qur’an do not only deduce the meaning of the text, but on the contrary, can induce the real meaning into the text. Interpret according to Hasan Hanafi means looking for something, object focus. Interpreting is to find something new among language text. It uses thematic method that is characteristic of interpretation by the scientific paradigm, which expresses the subjectivity emphasis of commitment interests and interpreter objective socially